2007
DOI: 10.1007/s10750-007-9173-3
|View full text |Cite
|
Sign up to set email alerts
|

Habitat influences snail community structure and trematode infection levels in a spring-fed river, Texas, USA

Abstract: The spring-fed Comal River in Texas, USA, has been impounded and channelized resulting mainly in a lentic environment with four headwater spring runs. We sampled two spring runs (lotic sites) and two lentic sites seasonally from April 2001 through April 2002 to assess (1) co-occurrence of native and exotic snail species (as determined by interspecific association), (2) the importance of habitat conditions in structuring relationships among these species, and (3) the distribution of snails infected with exotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…However, initially high densities of Marisa cornuarietis in Comal Springs were followed by a population crash in 1990 (Horne et al, 1992). In 2001-2002 the population density of Marisa cornuarietis in Comal Springs and Landa Lake was \1 m -2 (Tolley-Jordan & Owen, 2007). During our survey, the density of Marisa cornuarietis in Comal Springs and Landa Lake was also very low (only 2 individuals found).…”
Section: Impacts On Macrophytesmentioning
confidence: 50%
See 4 more Smart Citations
“…However, initially high densities of Marisa cornuarietis in Comal Springs were followed by a population crash in 1990 (Horne et al, 1992). In 2001-2002 the population density of Marisa cornuarietis in Comal Springs and Landa Lake was \1 m -2 (Tolley-Jordan & Owen, 2007). During our survey, the density of Marisa cornuarietis in Comal Springs and Landa Lake was also very low (only 2 individuals found).…”
Section: Impacts On Macrophytesmentioning
confidence: 50%
“…Neck (1984) also suggested that Marisa cornuarietis impacts E. comalensis in the San Marcos River. Melanoides tuberculatus and T. granifera also co-occur with E. comalensis in the Comal River, but apparently differ in their habitat use, with E. comalensis preferring higher flows in lotic habitats (Tolley-Jordan & Owen, 2007). We found that in some localities, very low densities of M. tuberculatus were associated with high (over 4,000 m -2 ) densities of E. comalensis (e.g., Barton Springs in Austin, Travis Co).…”
Section: Impact On Native Mollusksmentioning
confidence: 60%
See 3 more Smart Citations